2014
DOI: 10.1016/j.atherosclerosis.2014.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a: A player in the pathogenesis of atherosclerosis and other inflammatory disorders

Abstract: Objective The objective of this article is to review the current literature on Wnt5a and its signaling mechanism, along with its role in atherosclerosis. In addition, the significance of Wnt5a as a diagnostic marker and a potential therapeutic target is reviewed. Wnt5a, a secreted glycoprotein, belongs to a family of highly conserved proteins that regulate important processes such as cell fate specification, embryonic development, cell proliferation, migration, and differentiation in a variety of organisms. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 71 publications
3
80
0
Order By: Relevance
“…However, we found by gene expression analysis that Fzd5, but not Wnt5a, was upregulated by Ehrlichia, suggesting that Ehrlichia regulates the expression of Wnt5a receptor instead of Wnt5a itself, although Wnt5a does appear to be important for bacterial survival after entry. Wnt5a can bind to different classes of receptors and coreceptors, but Wnt5a signals primarily through the noncanonical pathway, where it mediates cell proliferation, adhesion, and movement (56). However, the role of Wnt5a in canonical signaling is still unclear, due to its complex nature.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found by gene expression analysis that Fzd5, but not Wnt5a, was upregulated by Ehrlichia, suggesting that Ehrlichia regulates the expression of Wnt5a receptor instead of Wnt5a itself, although Wnt5a does appear to be important for bacterial survival after entry. Wnt5a can bind to different classes of receptors and coreceptors, but Wnt5a signals primarily through the noncanonical pathway, where it mediates cell proliferation, adhesion, and movement (56). However, the role of Wnt5a in canonical signaling is still unclear, due to its complex nature.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical data have implicated aberrant WNT signaling in the pathogenesis of adult diseases such as cancer, arthritis, and cardiovascular disease. 14,16 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, depending on the receptor availability, Wnt5a can activate the noncanonical Wnt-Ca 21 and Wnt-planar cell polarity pathways, or activate the canonical pathway. 20 Further studies are needed to identify preponderant Wnt5a signaling pathways in our different models. Of note, the concentrations of Wnt5a that are commonly used in cell culture models are almost 100-fold superior to synovial fluid levels.…”
Section: Entheseal Cells Express Both Wnt5a and Its Receptormentioning
confidence: 99%
“…[18][19][20] Maeda et al indeed showed that among the 19 Wnt ligands, Wnt5a messenger RNA (mRNA) was the most upregulated Wnt member in mouse synovial tissues from collagen-induced arthritis. 19 In addition, although the canonical Wnt pathway appears to inhibit chondrocyte differentiation from mesenchymal precursors, 21,22 Wnt5a has been reported by several independent groups to induce chondrogenesis.…”
mentioning
confidence: 99%